Self-adjusting neck tractor - MA HAIYU; LU YONGYONG; DU PING; DU CHENGHUI (2024)
The invention discloses a self-adjusting neck tractor, and belongs to the field of neck tractors, the self-adjusting neck tractor comprises a fixing block, stretching assemblies are arranged at the upper end and the lower end of the fixing block, each stretching assembly comprises an air bag and an elastic corrugated pipe, the number of the air bags is two, and the elastic corrugated pipe is fixedly connected between the two air bags; a plurality of communicating holes are formed in the fixing block in a penetrating mode, the air bags at the upper end and the lower end of the fixing block communicate with each other through the communicating holes, and the lowest air bag of the four air bags is fixedly connected with an air guide pipe; a shell cover is connected to the lower portion of the air guide pipe. When the neck is stretched to the maximum stretching force, an L-shaped plate can cover the upper end of a connecting pipe at the moment, an air inflation bag cannot inflate the interior of the air bag at th